2019
DOI: 10.1016/j.chest.2018.10.024
|View full text |Cite
|
Sign up to set email alerts
|

A Sleep Medicine Curriculum for Pulmonary and Pulmonary/Critical Care Fellowship Programs

Abstract: BACKGROUND: Pulmonary medicine specialists find themselves responsible for the diagnosis and management of patients with sleep disorders. Despite the increasing prevalence of many of these conditions, many sleep medicine fellowship training slots go unfilled, leading to a growing gap between the volume of patients seeking care for sleep abnormalities and the number of physicians formally trained to manage them. To address this need, we convened a multisociety panel to develop a list of curricular recommendatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Additionally, the Specialty Curriculum Development Committee reviewed the local and international sleep medicine fellowship programme curricula in countries that already provide training and certification in sleep medicine. 20 , 21 , 22 , 23 , 24 , 25 , 26 Moreover, the committee contacted experts in sleep medicine training locally and in other countries to obtain information when needed.…”
Section: Methods For Curriculum Developmentmentioning
confidence: 99%
“…Additionally, the Specialty Curriculum Development Committee reviewed the local and international sleep medicine fellowship programme curricula in countries that already provide training and certification in sleep medicine. 20 , 21 , 22 , 23 , 24 , 25 , 26 Moreover, the committee contacted experts in sleep medicine training locally and in other countries to obtain information when needed.…”
Section: Methods For Curriculum Developmentmentioning
confidence: 99%
“…Inspiring the pipeline to commit to additional training in sleep will be critical to the health of our specialty, particularly because fellowship training has been required for board certification in sleep medicine since 2013. 3…”
Section: Improvement Of Sleep Medicine Educationmentioning
confidence: 99%
“…A multispecialty sleep medicine approach that embraces a diversity of specialty perspectives may also increase the number of specialists who select sleep medicine fellowship training. Inspiring the pipeline to commit to additional training in sleep will be critical to the health of our specialty, particularly because fellowship training has been required for board certification in sleep medicine since 2013 …”
Section: Improvement Of Sleep Medicine Educationmentioning
confidence: 99%
“…The graduate perspective therefore is one in which sleep medicine expertise has been developed or was present in the program. 8 Results indicated that most PM and PCCM PDs reported that their graduates could diagnose pulmonaryspecific sleep disorders such as OSA and central sleep apnea, sleep-related hypoventilation, and narcolepsy and insomnia; however, they indicate less confidence in ability to treat these disorders. Contrary to the PD survey, graduates for the most part felt comfortable managing sleep disorders and less comfortable diagnosing sleep disorders, particularly hypersomnias, parasomnias, and circadian rhythm disorders.…”
mentioning
confidence: 98%
“…Data from a 2014 survey of PCCM Fellowship PDs and graduates were collated to inform the construction of the roadmap to integrate sleep medicine education in the PCCM fellowship curriculum. 8 Of 162 programs, 44 completed the survey (ie, a 27% response rate with lower participation of Northwest and Southwest programs as well as sole PM vs PCCM programs). Smaller programs (ie, those with one to two fellows per year) appear to be underrepresented; therefore, generalizability and interpretation of the data presented should be placed into appropriate context.…”
mentioning
confidence: 99%